2014
DOI: 10.1002/ajp.22283
|View full text |Cite
|
Sign up to set email alerts
|

Social and personal information use by squirrel monkeys in assessing predation risk

Abstract: The threat of predation can significantly influence prey behaviors through altered perceptions of risk. Prey risk perception is constantly updated via collection of personal and social information about predators. Better understanding of the links between information availability, its use, and prey species' perception of risk will aid in explaining how animals adapt to predation. The goal of this study was to determine the environmental and social cues-available to prey via personal and social information, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…Most animals engage in some form of social interaction (Krause et al 2002; Frank 2007; Clutton-Brock 2016). These interactions frequently provide opportunity for gaining social information (Danchin et al 2004; Laland 2004; McGregor 2005; Allen et al 2013; Aplin et al 2015), whether it be the location of new food sources (Aplin et al 2012; Kendal et al 2015; Berdahl et al 2018; Nöbel et al 2018) or predation risk (Beauchamp et al 2012; Crane and Ferrari 2013; Frechette et al 2014). However, interacting with others can also be costly, with one of the primary costs being the risk of infection with pathogens or parasites (Daszak et al 2000; Stattner and Vidot 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Most animals engage in some form of social interaction (Krause et al 2002; Frank 2007; Clutton-Brock 2016). These interactions frequently provide opportunity for gaining social information (Danchin et al 2004; Laland 2004; McGregor 2005; Allen et al 2013; Aplin et al 2015), whether it be the location of new food sources (Aplin et al 2012; Kendal et al 2015; Berdahl et al 2018; Nöbel et al 2018) or predation risk (Beauchamp et al 2012; Crane and Ferrari 2013; Frechette et al 2014). However, interacting with others can also be costly, with one of the primary costs being the risk of infection with pathogens or parasites (Daszak et al 2000; Stattner and Vidot 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, when group size is small, predation risk generally increases (Hamilton 1971), and individuals should more often respond to alarm calls (Proctor et al 2001). Perceived risk also increases with habitat density (Whittingham and Evans 2004;Embar et al 2011), and receivers therefore increase their responsiveness to alarm calls as lines of sight become more interrupted (Enstam and Isbell 2004;Frechette et al 2014). In addition, prior information about current predation risk can influence alarm-call responses.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial cohesion is important for the stability of animal groups and for effective social information transfer about risks or resources (Evans et al 2016;Frechette et al 2014), but local environmental conditions may affect the costs and benefits of remaining near groupmates. Cohesion in samangos is an apparently flexible characteristic which changes reactively to encounters with competing groups but not to immediate predation risk from eagles.…”
Section: Discussionmentioning
confidence: 99%
“…Habitat attributes, including horizontal visibility and canopy cover are often associated with predation risk (Fortin et al 2009) and the ability of individual animals to monitor one another (Fernández-Juricic & Kacelnik, 2004;Frechette, Sieving, & Boinski, 2014) but our models that included interactions between location-specific risk or risky events and habitat attributes (models 2, 7-8) had relatively low weights. This was unexpected because previous studies of predation on forest primates indicated that crowned eagles often attacked where canopy cover was relatively low (Shultz, 2001) and previous studies on this population indicated that understory visibility was a significant predictor of perceived risk (Coleman & Hill, 2014;Emerson et al 2011).…”
Section: Additional Ecological Variablesmentioning
confidence: 99%